2004
DOI: 10.2134/jeq2004.4760
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ground Water Quality in an Irrigated Area of Southern Alberta

Abstract: Few studies have documented spatial and temporal variations in ground water quality in areas with high densities of animal farming operations (AFOs), or the long-term effects on surface-water quality. Changes in ground water quality were characterized in an irrigated area with a high density of AFOs in southern Alberta, Canada to evaluate the effect on ground water quality of manure application to fields. Fifty-five piezometers in the oxidized zone were sampled once or twice annually from 1995 to 2001, and tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 29 publications
6
50
0
3
Order By: Relevance
“…Repeated manure applications on land near CFOs can cause nutrient accumulation in soil above crop requirements (Sharpley et al 1998). Studies in Alberta have shown that repeated application of large rates of cattle manure causes excess nutrient accumulation in soil (Chang and Janzen 1996;Rodvang et al 2004;Chang et al 2005;Olson et al 2009). Excess nutrients are subject to loss through a variety of mechanisms and pose a risk to environmental quality, with water quality being of particular concern (Ribaudo et al 2003;Toth et al 2006).…”
Section: Mots Clé Smentioning
confidence: 99%
“…Repeated manure applications on land near CFOs can cause nutrient accumulation in soil above crop requirements (Sharpley et al 1998). Studies in Alberta have shown that repeated application of large rates of cattle manure causes excess nutrient accumulation in soil (Chang and Janzen 1996;Rodvang et al 2004;Chang et al 2005;Olson et al 2009). Excess nutrients are subject to loss through a variety of mechanisms and pose a risk to environmental quality, with water quality being of particular concern (Ribaudo et al 2003;Toth et al 2006).…”
Section: Mots Clé Smentioning
confidence: 99%
“…Moreover, almost half of those operations are large beef producers that are concentrated in the northern part of this district known as the "Feedlot Alley" [24]. Studies show that one feedlot may have as many as 25,000 cattle [19,24]. The sheer size of these operations and the livestock density has raised questions about environment, drinking water quality and threats to public health [8,17].…”
Section: Study Site Descriptionmentioning
confidence: 99%
“…A five-year surface water assessment study conducted by Saffran (2005) of the Oldman River Basin, the region's primary water source, found that this river has a high nitrate and coliform bacteria concentration that exceeds Canadian drinking water guidelines at all levels throughout the year [20]. Similarly, Rodvang et al (2004), in a study of ground water quality in an irrigated area of southern Alberta, observed that shallow ground water discharges cause nitrate and chloride levels in the Oldman River to increase by factors of at least 4.3 and 1.3, respectively, with more significant effects in smaller streams and under low-flow conditions [19]. Southern Alberta, which is primarily known for its dry land farming combined with an elaborate field crop irrigation system, also has the highest incidence of E coli O157:H7 contagion in the country [17,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manure storage structures are commonly made of mortarcovered bricks or precast concrete [1]. The degradation of these structures can cause the contamination of soils and underground water [2], constituting an environmental problem.…”
Section: Introductionmentioning
confidence: 99%